Electron cyclotron maser instability by evolving fast electron beams in the flare loops - Tang, J. F.; Wu, D. J.; Chen, L.; Tan, C. M.; Wang, J. B. (Frontiers in Astronomy and Space Sciences, 2024)
The electron-cyclotron maser instability (ECMI) stands as a pivotal coherent radio emission mechanism widely implicated in various astrophysical phenomena. In the context of solar activity, ECMI is primarily instigated by energetic electrons generated during solar eruptions, notably flares. These electrons, upon leaving the acceleration region,traverse the solar atmosphere, forming fast electron beams (FEBs) along magnetic field lines. It is widely accepted that as these FEBs interact with the ambient plasma and magnetic fields, they give rise to radio and hard X-ray emission. Throughout their journey in the plasma, FEBs undergo modifications in their energy spectrum and velocity spatial distribution due to diverse energy loss mechanisms and changes in ambient plasma parameters. In this study, we delve into the impact of the evolving energy spectrum and velocity anisotropic distribution of FEBs on ECMI during their propagation in flare loops. Our findings indicate that if we solely consider the progressively flattened lower energy cutoff behavior as FEBs descend along flare loops, the growth rates of ECMI decrease accordingly. However, when accounting for the evolution of ambient magnetic plasma parameters, the growth rates of ECMI increase as FEBs delve into denser atmosphere. This underscores the significant influence of the energy spectrum and velocity anisotropy distribution evolution of FEBs on ECMI. Our study sheds light on a more comprehensive understanding of the dynamic spectra of solar radio emissions.